Effects of Different Harvest Times on the Maturity of Polyphenols in Two Red Wine Grape Cultivars (Vitis vinifera L.) in Qingtongxia (China) - Zhou, Y.; Su, P.; Yin, H.; Dong, Z.; Yang, L.; Yuan, C. (South African Journal of Enology and Viticulture, 2018)
Due to the special climate conditions in the Qingtongxia region, grapes are high in sugar and low in titratable acidity from the stages of ripening. Therefore, the common methods used for determining the maturity of grapes, which depend on the ratio of sugar and titratable acidity in other regions, are inappropriate in Qingtongxia. This research was done in order to seek for a simple and convenient method of determining the optimal harvest time of grapes, further providing some theoretical basis for improving the quality of wine in Qingtongxia. Phenolic contents and some basic physico-chemical parameters of Merlot and Pinot Noir were evaluated during different ripening stages. The results showed that a different harvest time significantly affects the phenolic contents and physico-chemical parameters of Merlot and Pinot Noir. The total contents of anthocyanins in skins and total contents of phenolic in seeds was screen out as two important indexes to evaluate the maturity of polyphenols, in order to better improve the quality of grape and wine.